Polyamide Microparticles with Immobilized Enological Pectinase as Efficient Biocatalysts for Wine Clarification: The Role of the Polymer Support - Sandra C. Oliveira; Samuel M. Araújo; Nadya V. Dencheva; Zlatan Z. Denchev (Molecules)
Free pectinase is commonly employed as a biocatalyst in wine clarification; however, its removal, recovery, and reuse are not feasible. To address these limitations, this study focuses on the immobilization of a commercial pectinolytic preparation (Pec) onto highly porous polymer microparticles (MPs). Seven microparticulate polyamide (PA) supports, namely PA4, PA6, PA12 (with and without magnetic properties), and the copolymeric PA612 MP, were synthesized through activated anionic ring-opening polymerization of various lactams. Pectinase was non-covalently immobilized on these supports by adsorption, forming Pec@PA conjugates. Comparative activity and kinetic studies revealed that the Pec@PA12 conjugate exhibited more than twice the catalytic efficiency of the free enzyme, followed by Pec@PA6-Fe and Pec@PA4-Fe. All Pec@PA complexes were tested in the clarification of industrial rosé must, demonstrating similar or better performance compared to the free enzyme. Some immobilized biocatalysts supported up to seven consecutive reuse cycles, maintaining up to 50% of their initial activity and achieving complete clarification within 3–30 h across three consecutive cycles of application. These findings highlight the potential for industrial applications of noncovalently immobilized pectinase on various polyamide microparticles, with possibilities for customization of the conjugates’ properties.